Implementación y desarrollo de prácticas de automatización a través de un módulo didáctico con el PLC S7-1200 aplicados a sistemas de la agroindustria - Chulde Marcalla, Jhon Anderson (2017)
The objective of this research project is to implement a didactic module with the PLC Simatic S7-1200 applied to agroindustrial systems, which have command-control and automation devices. In the automation of industrial processes where the PLC plays an important role, the S7-1200 model is compact and powerful particularly in terms of real-time response, extraordinary connectivity and all kinds of facilities in software and hardware handling. All this we can develop within the educational environment in which it will allow to implement didactic processes, that can be coupled together and simulate a real industrial environment. Allowing complementing the theoretical knowledge with the practices that will be realized. The objective of this project is the implementation and development of automation practice through a didactic module with the PLC Simatic S7-1200 to be is a controller that offers the flexibility and power necessary to control a great variety of devices in different needs of automation. Thanks to its compact design, flexible configuration and extensive set of instructions, the S7-1200 is ideal for controlling a wide variety of agroindustrial applications to facilitate the learning process in the research laboratory of the Electromechanical Engineering career at the Technical University of Cotopaxi La Maná extension in 2017.